2021
DOI: 10.1111/jog.14733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, treatment, and outcomes associated with vaginal intraepithelial neoplasia: A retrospective study of 118 patients

Abstract: The incidence of vaginal intraepithelial neoplasia (VAIN) is increasing annually; however, the reported values are likely underestimated. Risk factors for VAIN include advanced age, human papillomavirus (HPV) infection, history of hysterectomy, and simultaneous or previous cervical intraepithelial neoplasia (CIN) or cervical cancer cervical cancer. The most common presentation is abnormal cytology without clinical symptoms. Despite various treatment modalities available, the rate of disease recurrence is high,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
2
20
0
2
Order By: Relevance
“…Studies have reported that low-grade VAIN has a tendency to self-heal, but not all can be reversed with some of the lesions persist or even progress [ 13 ]. Risk factors for VaIN include hrHPV infection, CIN, cervical cancer, and hysterectomy [ 14 ]. It is reported that most VaIN patients are complicated with I-II CIN [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that low-grade VAIN has a tendency to self-heal, but not all can be reversed with some of the lesions persist or even progress [ 13 ]. Risk factors for VaIN include hrHPV infection, CIN, cervical cancer, and hysterectomy [ 14 ]. It is reported that most VaIN patients are complicated with I-II CIN [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common risk factor for VaIN is persistent HPV infection, and this is the main factor associated with persistence, recurrence, and progression. The distribution of HPV subtypes varies, but HPV 16 is the subtype implicated in the majority of high-grade dysplasia 3. Additional suggested risk factors for progression to carcinoma are a history of hysterectomy for cervical dysplasia/carcinoma and a history of pelvic radiation therapy 4,7.…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…The distribution of HPV subtypes varies, but HPV 16 is the subtype implicated in the majority of high-grade dysplasia. 3 Additional suggested risk factors for progression to carcinoma are a history of hysterectomy for cervical dysplasia/carcinoma and a history of pelvic radiation therapy. 4,7 Overall, the rate of progression to invasive cancer has been found to be somewhere between 2% and 8% in several retrospective studies.…”
Section: Demonstrated a Median Age Of Diagnosis Ofmentioning
confidence: 99%
See 2 more Smart Citations